The SLE transcriptome exhibits evidence of chronic endotoxin exposure and has widespread dysregulation of non-coding and coding RNAs. - Lihua Shi; Zhe Zhang; Angela M Yu; Wei Wang; Zhi Wei; Ehtisham Akhter; Kelly Maurer; Patrícia Costa Reis; Li Song; Michelle Petri; Kathleen E Sullivan (PLoS ONE)
Background Gene expression studies of peripheral blood mononuclear cells from patients with systemic lupus erythematosus (SLE) have demonstrated a type I interferon signature and increased expression of inflammatory cytokine genes. Studies of patients with Aicardi Goutières syndrome, commonly cited as a single gene model for SLE, have suggested that accumulation of non-coding RNAs may drive some of the pathologic gene expression, however, no RNA sequencing studies of SLE patients have been performed. This study was designed to define altered expression of coding and non-coding RNAs and to detect globally altered RNA processing in SLE. Methods Purified monocytes from eight healthy age/gender matched controls and nine SLE patients (with low-moderate disease activity and lack of biologic drug use or immune suppressive treatment) were studied using RNA-seq. Quantitative RT-PCR was used to validate findings. Serum levels of endotoxin were measured by ELISA. Results We found that SLE patients had diminished expression of most endogenous retroviruses and small nucleolar RNAs, but exhibited increased expression of pri-miRNAs. Splicing patterns and polyadenylation were significantly altered. In addition, SLE monocytes expressed novel transcripts, an effect that was replicated by LPS treatment of control monocytes. We further identified increased circulating endotoxin in SLE patients. Conclusions Monocytes from SLE patients exhibit globally dysregulated gene expression. The transcriptome is not simply altered by the transcriptional activation of a set of genes, but is qualitatively different in SLE. The identification of novel loci, inducible by LPS, suggests that chronic microbial translocation could contribute to the immunologic dysregulation in SLE, a new potential disease mechanism.